Solubility of anhydrite and gypsum at temperatures below 100°C and the gypsum-anhydrite transition temperature in aqueous solutions: a re-assessment - Voigt, Wolfgang; Freyer, Daniela (Frontiers in Nuclear Engineering, 2023)
Anhydrite and gypsum are omnipresent in sedimentary rocks of all types. They occur as massive layers or are distributed within other geological formations as in clays. Understanding the conditions of formation and the stability of the hydrated and anhydrous form of calcium sulfate is crucial in an elucidation of the genesis of the geological formations envisaged as potential host rock for radioactive waste disposal. Estimations of the temperature, where gypsum is dehydrated to anhydrite in water vary between 30°C and 60°C. The extremely slow crystallization kinetics of anhydrite at T < 90°C prevents a direct determination of this transition temperature. In the present work the different approaches to fix this temperature are discussed. It is shown that careful assessment of solubility data and calorimetric measurements yields a transition temperature of 42°C ± 1°C. For results essentially deviating from this value methodic deficiencies are revealed and discussed. Thus, a long-standing discussion about the thermodynamic aspect of the gypsum-anhydrite conversion can be closed, not the kinetic part.